Whole‐Mount In Situ Hybridization in Post‐Implantation Staged Mouse Embryos. Issue 2 (21st May 2020) - Barratt, Kristen S.; Arkell, Ruth M.
Abstract: Understanding RNA expression in space and time is a key initial step in dissecting gene function. The ability to visualize gene expression in whole‐tissue or whole‐specimen preparations, called in situ hybridization (ISH), was first developed 50 years ago. Two decades later, these protocols were adapted to establish robust methods for whole‐mount ISH to murine embryos. The precise protocols vary somewhat between early‐gestation and mid‐gestation mouse embryos; the protocol presented here is optimal for use with post‐implantation stage mouse embryos (stages 5.5–9.5 dpc). Routine uses of whole‐mount ISH include documenting the wild‐type expression pattern of individual genes and comparison of the expression pattern of signature genes (i.e., those that identify particular cells and tissues within an embryo) between wild‐type and mutant embryos as part of a phenotyping experiment. This technique remains a mainstay of developmental biology studies and complements the massively parallel assessment of gene expression from dissociated tissues and cells via RNA‐sequencing techniques. © 2020 by John Wiley & Sons, Inc. Basic Protocol 1 : Dissection of post‐implantation (5.5‐9.5 dpc) murine embryos Basic Protocol 2 : Whole‐mount in situ hybridization in post‐implantation embryos Basic Protocol 3 : Visualization of post‐WMISH embryos Support Protocol 1 : Creation of siliconized glass pipettes Support Protocol 2 : Creation of embryo powder